Effect of Chronic Exercise Training on Blood Lactate Metabolism Among Patients With Type 2 Diabetes Mellitus: A Systematic Review and Meta-Analysis - Zhao, Tong; Le, Shenglong; Freitag, Nils; Schumann, Moritz; Wang, Xiuqiang; Cheng, Sulin (Frontiers in Physiology, 2021)
Purpose: To assess the effect of chronic exercise training on blood lactate metabolism at rest (i.e., basal lactate concentrations) and during exercise (i.e., blood lactate concentration at a fixed load, load at a fixed blood lactate concentration, and load at the individual blood lactate threshold) among patients with type 2 diabetes mellitus (T2DM). Methods: PubMed (MedLine), Embase, and Web of Science were searched. Studies using chronic exercise training (i.e., ≥ 4 weeks) and assessed blood lactate concentrations at rest and during exercise among T2DM patients were included. Results: Thirteen studies were eligible for systematic review, while 12 studies for meta-analysis. Chronic exercise training had no significant effect on changes in basal blood lactate concentrations from baseline to post-intervention (standard mean difference (SMD) = -0.20; 95% CI, -0.55 to 0.16; p = 0.28; I2 = 12%), while blood lactate concentration at a fixed load significantly decreased (SMD = -0.73; 95% CI, -1.17 to -0.29; p = 0.001) and load at a fixed blood lactate concentration increased (SMD = 0.40; 95% CI, 0.07 to 0.72; p = 0.02). No change was observed in load at the individual blood lactate threshold (SMD = 0.28; 95% CI, -0.14 to 0.71; p = 0.2). Conclusion: Chronic exercise training does not statistically affect basal blood lactate concentrations; however, it may decrease the blood lactate concentrations during exercise, indicating improvements of physical performance capacity which is beneficial for T2DM patients’ health in general. Why chronic exercise training did not affect basal blood lactate concentrations needs further investigation.